2020
DOI: 10.3390/su12177023
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Indo-Pacific Climate Variability on Rice Productivity in Bihar, India

Abstract: The impact of Indo-Pacific climate variability in the South Asian region is very pronounced and their impact on agriculture is very important for the Indian subcontinent. In this study, rice productivity, climatic factors (Rainfall, Temperature and Soil Moisture) and associated major Indo-Pacific climate indices in Bihar were investigated. Bihar is one of the major rice-producing states of India and the role of climate variability and prevailing climate indices in six events (between 1991–2014) with severer th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 73 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…Climate variability and seasonality are major determinants of agricultural productivity in Bihar. Given the dominant rainfed conditions of rice-wheat systems, while the productivity of the dominant kharif rice is highly determined by anomalies in monsoon rains, temperatures strongly determine the productivity of wheat in winter [12,17].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Climate variability and seasonality are major determinants of agricultural productivity in Bihar. Given the dominant rainfed conditions of rice-wheat systems, while the productivity of the dominant kharif rice is highly determined by anomalies in monsoon rains, temperatures strongly determine the productivity of wheat in winter [12,17].…”
Section: Study Areamentioning
confidence: 99%
“…Much attention has been paid to summer monsoon rains and mean temperatures variability over the IGP as determinants of crops productivity [5,12]. However, less emphasis has been placed on the impacts of adverse temperatures on rice-wheat systems and on the development of adaptation strategies based on management decisions.…”
Section: Introductionmentioning
confidence: 99%
“…India is a tropical country with the summer monsoon season in June-July-August-September (hereafter JJAS). JJAS is generally defined as the monsoon season in India because the major chunk of the summer monsoon rainfall amount is obtained during this period of the year (Sahu et al, 2020;Saini and Sahu, 2021). India has a huge dependence on the behavior of the monsoon system from its onset to withdrawal (Prasad and Hayashi, 2005;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In Morocco, Bouras et al [30] assessed climate change impacts on irrigation water requirements and wheat grain and found that future irrigation water demand and grain yields would decrease by 13-42% and 7-30%, respectively, during the 2050s and 2090s for RCP4.5 and RCP8.5, respectively. Studies have shown that agricultural production has been reduced due to climate change impacts in India [31,32]. Such yield declines were attributed to (1) reduced rainfall, (2) altered distribution of seasonal rainfall, particularly during critical crop growth stages, (3) severe heat stress events around anthesis, and (4) increased rates of crop development causing early maturity (e.g., [33,34]).…”
Section: Introductionmentioning
confidence: 99%